Endotracheal Tube Cuff Pressure Management: An Observational Study Guided by the SEIPS Model. Issue 2 (March 2022) - Kebapci, Ayda; Ozkaynak, Mustafa
Abstract : Introduction: The aim of the rigorous endotracheal tube cuff pressure (ETTCP) management is to maintain cuff pressures within the recommended values during the mechanical ventilation period. However, hyperinflation or hypoinflation of cuff has been reported because of inconsistent clinical practices in intensive care unit (ICU) settings. Furthermore, there is no available best evidence for clinical decision-making regarding the ETTCP management provided by international institutes. Purpose: The aim of this study was to examine the ETTCP management work system in ICU settings in urban hospitals of Turkey and the United States using the Systems Engineering Initiative for Patient Safety model. Methods: This was a direct observational, prospective field study, in which the COREQ (Consolidated Criteria for Reporting Qualitative Research) tool was used. The direct observations and follow-up interviews were conducted, and the results were reported using the Systems Engineering Initiative for Patient Safety model. Results: We identified important characteristics of the ETTCP management work system in each of the 4 ICU and differences across the settings. Conclusion: Common use of the evidence-based and internationally used protocols may standardize the management of ETTCP, improve communication among ICU staff, and promote desired patient outcomes. Relevance to Clinical Practice: There is a need for developing strategies to provide standardized ETTCP management and to improve patient's quality of care. To improve the patient outcomes and quality of care, ICU managers should consider clear expectations for ETTCP management in each job description, structured and evidence-based protocols, and effective communication among disciplines and provide teaching opportunities to encourage physicians, nurses, and respiratory therapists to meet their educational needs.